Lifting Structural Assessment of a Working Basket Installed on a Hydraulic Workover Unit (EHR 340K) - Calista Maharani; Luh Putri Adnyani; Nurmawati; Muhammad Khaisar Wirawan; Indah Melati Suci; Ahmad Azwar Mas'ud; Muhammad Abdul Ghofur Al Hakim; Muhammad Iqra Prasetya (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
The Hydraulic Workover Unit (HWU) is a critical piece of equipment in the oil and gas industry, widely used for well maintenance operations. One of the main components of the HWU is the working basket, which serves as a designated workspace for personnel and must be transported through a lifting process prior to installation on an offshore platform. Lifting operations involve significant risks and therefore require thorough technical analysis to ensure structural safety and reliability. This study aims to analyze the structural behavior of the working basket of the HWU EHR 340K during lifting operations. The analysis was conducted using SACS software. The results indicate that all structural members satisfy the unity check requirements with values less than one, and that the sling forces remain within the allowable capacity limits. Consequently, the proposed lifting configuration is considered safe and suitable for implementation in the lifting process of the HWU working basket.